APPLICATION OF R/S-METHOD IN THE ANALYSIS OF THE NBU DISCOUNT RATE DYNAMICS - Колодій, Сергій; Гаряга, Леся; Руденко, Микола (Socio-economic relations in the digital society, 2019)
The expediency of using fractal analysis in studying the dynamics of the discount rate of the NBU have been researched in the article. The central bank’s rate is an important monetary policy tool. Th e dynamics of this indicator gives the “signal” of the market in relation to the optimal level of interest rates, which should contribute to the achievement of the objectives of monetary regulation. Forecasting and analyzing the dynamics of the discount rate is a prerequisite for realizing the objectives of the monetary policy transmission mechanism. In conditions of significant instability and volatility of both financial and real sectors of the economy, the most appropriate method for analyzing the dynamics of stochastic processes is a fractal analysis, in particular R/S-method that allows to detect the randomness or persistence of the time series. The average annual discount rate, taking into account the period of time during the year in which it operated has been calculated. The R/S analysis have been carried out and the Hurst indicator has been determined for the real average annual discount rate of the NBU. Th e Hurst index varies from 0.527 to 0.619, varying from 0.527 to 0.619, and increases with the widening of the range of observations, which means that there is no persistence and antipersistence, and suggests that the NBU discount rate has been used as a tool for regulating money supply as a result of a discrete monetary policy macroeconomic regulation. The R/S-analysis (the study period of the dynamics of the NBU discount rate is 22 years) suggests that the real average NBU discount rate is a stochastic variable and can be used as a result or explanatory indicator in econometric studies. It should be noted that with an increase in the range of research of the dynamics of the discount rate, there are insignificant signs of persistence, which indicates a certain numbness of the series and a weakening of the expressed trend.